The moderating role of gender in the effect of self-monitoring personality trait on emotional labor strategies - Sunday Samson Babalola; Chiyem Lucky Nwanzu (Cogent Business & Management, 2022)
This study investigated the effect of self-monitoring on emotional labor strategies (surface acting and deep acting) and the moderating role of gender in development. In anchoring the relationship between self-monitoring and emotional labor, the conservation of resources theory was used, while the moderating role of gender was based on sociocultural theory. A sample of 312 employees from the health and communication sectors provided the analyzed data. Data analysis was based on regression analysis (complemented with the PROCESS tool). The results showed positive self-monitoring (surface and deep acting) effects on emotional labor. More so, gender was found to moderate the impact of self-monitoring on surface acting strategy but not on deep acting strategy. The practical implication of this study is to provide information on the value of self-monitoring in improving, especially in men, the ability to express emotional labor.
Keywords: 650; gender; conservation of resources theory; emotional labor; self-monitoring; surface acting